Clinical Features, Therapeutic Trends, and Outcome of Giant Prolactinomas: A Single-Center Experience Over a 12-Year Period. (June 2020) - Almalki, Mussa H; Aljohani, Naji; Alzahrani, Saad; Almohareb, Ohoud; Ahmad, Maswood M; Alrashed, Abdullah A; Alshahrani, Fahad; Mahmood Buhary, Badurudeen
Background: Management of giant prolactinomas presents a different challenge than the management of traditional prolactinomas. Objective: The aim of this study was to report the largest long-term single-center study of giant prolactinomas to analyze their clinical features; define epidemiological characteristics, comorbidities, complications, treatment outcomes; and to demonstrate our experience with long-term cabergoline (CAB) treatment of these giant tumors. Methods: A retrospective case study and clinical review of patients presenting with giant prolactinomas in the pituitary clinic at King Fahad Medical City (KFMC), Riyadh, Saudi Arabia, in the period between 2006 and 2018 were included in the study. Of the charts reviewed, 33 patients (24 men; 9 women) with age of diagnosis between 18 and 63 years (mean = 37.21 years) met the selection criteria for giant prolactinomas. Result: The most common presenting features include headache (87.8%), visual defects (69.7%), and hypogonadism (51.5%). The baseline means serum prolactin (PRL) level was extremely high for both sexes (95 615.03 nmol/L), which eventually decreased by as much as 95.4% after CAB treatment. Serum PRL concentrations completely normalized in 11 patients and significantly reduced in 22 patients. The mean tumor volume at baseline was 42.87 cm 3, whereas the mean posttreatment tumor volume was 3.42 cm 3 (no residual tumor in 2 patients, while in others, it ranged from 0.11 to 16.7 cm 3 ) at the last follow-up visit. The mean change in tumor volume was 88.84%. Tumor volume decreased by an average of 92% for men and 80.4% for women. One patient had no tumor size change with CAB (3.5 mg thrice a week) or radiotherapy and required surgery. The response rate (remission after medical therapy alone) in this series was 84.84%. Conclusions: Findings reinforce results from our previous study that CAB provides dramatic clinical improvements with an excellent safety profile. The CAB should, therefore, be considered as the primary therapy for giant prolactinomas.